People's Participation - a Vital Component in Management of Gir Protected Area - Srivastava, Aseem (Indian Forester, 1997)
The collaborative efforts of the people and the Forest Department have paid rich dividends in changing the scenario of Gir. But increasing the biotic pressure demands more to be done economically, environmentally and in friendly manner to preserve and protect the ecosystem.